Digital restoration using volumetric scanning - Seales, W. B.; Lin, Yun (Proceedings of the 4th ACM/IEEE-CS Joint Conference on Digital Libraries, 2004)
In this paper we present a new, nondestructive method for revealing inaccessible text buried within damaged books and scrolls. The method is based on volumetric scanning followed by data modeling and physically-based simulation. We show by experiment that it is possible to recover readable text from objects without physically opening or damaging them. In handling damaged collections, conservators often face a choice between two frustrating alternatives: indefinite preservation without analysis, or irreversible physical harm for the sake of potential discovery. We believe that this work creates a new opportunity that embraces both the need to preserve and the possibility for complete analysis.